Women and the civil rights movement, 1954-1965 - Houck, Davis W.; Dixon, David E. (University Press of Mississippi, 2009)
Presents thirty-nine full-text addresses by women who spoke out while the struggle for civil rights was at its most intense. Many are published or transcribed from audio tape for the first time. Each speech is preceded by an introduction of the speaker and occasion that highlights key biographical and background details. The collection also provides a general introduction that places these public addresses in context.